In vitro antiplasmodial, antiamoebic, and cytotoxic activities of a series of bisbenzylisoquinoline alkaloids. - Marshall, S J (1994)
Twenty-four bisbenzylisoquinoline alkaloids were screened for antiplasmoidal, antiamoebic, and cytotoxic activities by use of in vitro microtests. Eight of the alkaloids had antiplasmodial activity, with a 50% inhibitory concentration (IC50) of less than 1 microM against a multidrug-resistant strain of Plasmodium falciparum (chloroquine had an IC50 of 0.2 microM). The three alkaloids most active against Entamoeba histolytica, aromoline, isotrilobine, and insularine, had IC50s of 5 to 11.1 microM (metronidazole had an IC50 of 1.87 microM). None of the 24 bisbenzylisoquinoline alkaloids exhibited significant cytotoxicity against the KB cell line, the most toxic being berbamine, with an IC50 of 17.8 microM (the IC50 of podophyllotoxin was 0.008 microM). Bisbenzylisoquinoline alkaloids merit further investigation as potential novel antimalarial agents.